Continuous beta-lactam infusion in critically ill patients: the clinical evidence - Abdul Aziz, Mohd. Hafiz; Dulhunty, Joel M.; Bellomo, Rinaldo; Lipman, Jeffrey; Roberts, Jason A. (Springer-Verlag Berlin Heidelberg, 2012)
There is controversy over whether traditional intermittent bolus dosing or continuous infusion of beta-lactam antibiotics is preferable in critically ill patients. No significant difference between these two dosing strategies in terms of patient outcomes has been shown yet. This is despite compelling in vitro and in vivo pharmacokinetic/pharmacodynamic (PK/PD) data. A lack of significance in clinical outcome studies may be due to several methodological flaws potentially masking the benefits of continuous infusion observed in preclinical studies. In this review, we explore the methodological shortcomings of the published clinical studies and describe the criteria that should be considered for performing a definitive clinical trial. We found that most trials utilized inconsistent antibiotic doses and recruited only small numbers of heterogeneous patient groups. The results of these trials suggest that continuous infusion of beta-lactam antibiotics may have variable efficacy in different patient groups. Patients who may benefit from continuous infusion are critically ill patients with a high level of illness severity. Thus, future trials should test the potential clinical advantages of continuous infusion in this patient population. To further ascertain whether benefits of continuous infusion in critically ill patients do exist, a large-scale, prospective, multinational trial with a robust design is required.